A BIBLIOMETRICS ANALYSIS ON MATHEMATICAL THINKING IN INDONESIA FROM SCOPUS ONLINE DATABASE WITH AFFILIATION FROM INDONESIA - Edi Supriyadi (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Developing students' mathematical thinking is one of the most important objectives of mathematics education. Mathematical thinking in Indonesia is the focus of this study, which presents the results of a bibliometric investigation. This study aims to determine the development of mathematical thinking research publications and the distribution of research publications by type of publication, research institutes, and scientific journals in Indonesia on the Scopus online database. This study aims to determine the development of mathematical thinking research publications and the distribution of research publications by type of publication, research institutes, and scientific journals in Indonesia on the Scopus online database. This research is quantitative and descriptive. By collecting data from research on mathematical thinking in Indonesia in scientific journals at Scopus. Bibliometrics R-tool and BiblioShiny were used in this study. According to the findings of this bibliometric study, publication on mathematical thinking attained its pinnacle in 2019, marking the year when it realized its full potential. The publication outcomes are dominated by conference series journals. Authors submit their work to these journals by attending international conferences. Research on mathematical thinking is being conducted at Universitas Pendidikan Indonesia at a higher level than at any other Indonesian university. Furthermore, it is anticipated that future studies will make use of Bradford's theorem in order to present data that is more accurate for the purpose of the development of bibliometric studies.